Population demographic tracking and estimation tool: a simulation-dashboard for urban redevelopment’s demographic implications in Israel - Levine, Daphna; Sussman, Shai; Aharon-Gutman, Meirav; Yavo Ayalon, Sharon (Frontiers in Built Environment, 2024)
This research introduces a pioneering methodology and user-friendly online dashboard for examining population shifts during urban redevelopment in Bat Yam, Israel, part of the Tel Aviv Metropolitan Area. The simulation tool, easily operated through scripts, predicts how redevelopment scenarios will impact household demographics over time. Its output, a population track-change CSV file, details demographic changes, aiding planners in understanding population dynamics at a household level. The accompanying online dashboard visually presents these changes, making the data accessible to policymakers and planners alike. Additionally, the tool's consideration of environmental factors enhances its applicability in identifying vulnerable populations and resilient communities amidst urban renewal. This user-friendly approach, compatible with existing planning tools, underscores the article's significance in advancing urban planning practice and addressing societal needs.